2018
DOI: 10.3390/ijms19123892
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of PPARγ Promoter Usage, Lipid Degradation Activity, and Gene Expression in Subcutaneous Adipose Tissue of Lean and Obese Swine

Abstract: Subcutaneous adipose tissue is a loose connective tissue specializing in the regulation of energy storage and metabolization. In domesticated pigs (Sus scrofa), the temporal development of subcutaneous adipose tissue is critical for meat production. However, the regulation of adipose tissue development remains unclear. Here, the subcutaneous adipose tissue development was characterized and compared in lean (Danish-Landrace) and obese (Min) pigs at juvenile and the juvenile-to-adult growth stages. Using RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…A study on several Chinese breeds as compared to Yorkshire breeds revealed upregulated expression of genes associated with immune response, oxidoreductase activity and biosynthetic process (e.g., acetyl-CoA biosynthetic process), whereas the expression of genes involved in fat oxidation was lower [89]. The study of Song et al [90] showed that genes associated with fatty acid degradation, mitochondrial functions and oxidoreductase activity were downregulated in indigenous Min pigs compared to in modern Landrace pigs. Similarly, genes related to mitochondrial energy and electron transport pathways were also downregulated in local Basque pigs compared to in Large White pigs [72].…”
Section: Comparison Of Mrna Transcriptome Of Subcutaneous Adipose Tissuementioning
confidence: 99%
“…A study on several Chinese breeds as compared to Yorkshire breeds revealed upregulated expression of genes associated with immune response, oxidoreductase activity and biosynthetic process (e.g., acetyl-CoA biosynthetic process), whereas the expression of genes involved in fat oxidation was lower [89]. The study of Song et al [90] showed that genes associated with fatty acid degradation, mitochondrial functions and oxidoreductase activity were downregulated in indigenous Min pigs compared to in modern Landrace pigs. Similarly, genes related to mitochondrial energy and electron transport pathways were also downregulated in local Basque pigs compared to in Large White pigs [72].…”
Section: Comparison Of Mrna Transcriptome Of Subcutaneous Adipose Tissuementioning
confidence: 99%
“…Min pig (Sus scrofa), a local breed in Northeastern China, has been characterized as prolific (14.35 piglets per birth) and a source of good meat, and has a strong resistance to poor feed quality and cold climate (Wang et al 2002;Song et al 2018). Furthermore, its good maternal temperament is another outstanding characteristic of the Min pig breed (Wang et al 2002).…”
Section: Min Pig; Mitochondrial Genome; Nucleus Herd; Species Conservmentioning
confidence: 99%
“…2002 ; Song et al. 2018 ). Furthermore, its good maternal temperament is another outstanding characteristic of the Min pig breed (Wang et al.…”
mentioning
confidence: 99%
“…Several previous studies both in vitro and vivo have shown an anti-inflammatory mechanism of ESWT, which treatment inhibited NF-κB activation and decreased oxygen radical production, leukocyte infiltration, chemokine expression, and pro-inflammatory cytokine expression 9 11 . In recent our study, shown ESWT down-regulated transforming growth factor beta 1 (TGF-β1) expression and reversed epithelial mesenchymal transition (EMT) in fibroblast derived from HTS 12 . The signal transduction associated with above events by ESWT is not clear.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, we reported the therapeutic effects of ESWT on scar pain and pruritus in burn patients with hypertrophic scar 19 , 20 , and showed that treatment changed the levels of hypertrophic scar-related molecules in fibroblasts derived from hypertrophic scars 12 . Examining the effect of extracorporeal shock waves on keratinocytes derived from hypertrophic scar tissue at the molecular level will provide important evidence about the effectiveness of this therapy for hypertrophic scar treatment.…”
Section: Introductionmentioning
confidence: 99%